Addressing Unmet Information Needs: Results of a Clinician-Led Consultation Service About Complementary and Alternative Medicine for Cancer Patients and Their Relatives. (December 2018) - Horneber, Markus; van Ackeren, Gerd; Fischer, Felix; Kappauf, Herbert; Birkmann, Josef
Purpose . To report on a telephone consultation service with cancer patients and their relatives about complementary and alternative medicine (CAM) between 1999 and 2011. Methods . We offered a Germany-wide, free-of-charge telephone consultation service about CAM led by oncology clinicians from a comprehensive cancer center. The consultations followed a patient-centered approach with the aim to provide guidance and evidence-based information. Sociodemographic, disease-related data as well as information about the consultations' content were collected in a standardized manner, and feedback questionnaires were sent out immediately after the consultations. Results . Overall, 5269 callers from all over Germany used the service (57% patients, 43% relatives). The "big 4" cancer types (breast, gastrointestinal, prostate, and lung) accounted for 55% of all calls. In 67% of calls, patients had just received the diagnosis or commenced anticancer therapy; 69% of patients had advanced or metastatic diseases. More than half of the callers (55%) had vague concerns like "what else can I do?" rather than specific questions related to CAM. The consultations covered a broad spectrum of issues from CAM therapies to cancer treatment and measures supportive of health, nutrition, and psychosocial support. Callers highly valued the service. Conclusions . Consulting about CAM addresses important unmet needs from cancer patients and their relatives. It provides clinicians with the opportunity to engage in open and supportive dialogues about evidence-based CAM to help with symptom management, psychological support, and individual self-care. Consulting about CAM cannot be separated from consulting about conventional care and should be provided from the beginning of the cancer journey.